Digital connectivity and sharing at school: Opportunities and security challenges of using social networking sites - Hina, S. (Institute of Electrical and Electronics Engineers Inc., 2017)
The hi-tech instigation of social media, powered and enhanced by the unique participation/collaboration pattern has initiated an epoch of in-depth research practices in education, government and the corporate sector. Social Networking Sites (SNS) are an example of Web 2.0 software that adheres to the participation/collaboration pattern with the capacity to connect people with similar demographics, interests, ideas, as well as similar educational, professional or social backgrounds. This study examines the perceived security and privacy on SNS along with the cyber safety education (acceptable usage policies) among stakeholders in schools (parents, teachers, students and school admin). A research framework has been established by incorporating a construct of intention to use SNS from the Technology Acceptance Model along with a unique combination of perceived security, perceived privacy, cyber safety education and trust constructs. Using reliable metrics from the literature, the research study validates that an enhanced sense of security and privacy positively affects users' trust in SNS. This paper highlights that the existence of a cyber-safety education among stakeholders also positively influences user trust in friends and eventually in positive intention for educational association. Moreover, secure and trusted intention to use SNS leads towards participation/collaboration between all stakeholders in the school environment. © 2017 IEEE.